Evaluating the role of trimetazidine in preventing myocardial injury and contrast-induced nephropathy in patients undergoing percutaneous coronary interventions - Anshul Jain; Amresh Kumar Singh; Sudarshan Kumar Vijay; Bhuwan Chandra Tiwari; Ashish Jha; Naveen Jamwal (Heart India)
Background: Myocardial ischemia and contrast-induced nephropathy (CIN) are critical complications in patients undergoing percutaneous coronary intervention. Trimetazidine (TMZ), a metabolic modulator with cardioprotective and renal protective properties, may reduce these risks. This study aimed to evaluate the role of TMZ in preventing periprocedural myocardial injury and CIN, alongside its impact on left ventricular function, angina frequency, and quality of life. Materials and Methods: This single-center, prospective, observational study included 300 patients undergoing PCI with drug-eluting stents and divided into two groups based on receiving TMZ or not. Baseline and postprocedural assessments included serum troponin I, CK-MB, serum creatinine, estimated glomerular filtration rate (eGFR), left ventricular ejection fraction (LVEF), and Seattle Angina Questionnaire (SAQ) scores. Statistical analyses compared outcomes between the groups, with P < 0.005 considered statistically significant. Results: The TMZ group exhibited significantly lower troponin I and CK-MB levels post-PCI, indicating reduced PMI. LVEF improved significantly more in the TMZ group at 3 months (P = 0.002). The incidence of CIN was significantly lower in the TMZ group (P = 0.048). Angina frequency and quality of life showed greater improvement in the TMZ group as reflected by SAQ scores. Serum creatinine and eGFR changes further supported TMZ’s renal protective effects. Conclusion: The findings highlight TMZ’s potential as an adjunctive therapy in PCI, emphasizing its underutilized role in the clinical practice.